Audit Forensik sebagai Upaya Pemberantasan Korupsi Partai Politik : Komparisi Indonesia dan Nigeria - Sari, Dini Wininta (Fakultas Hukum Universitas Andalas, 2024)
Indonesia's political party reporting especially during the election period is not yet accountable, transparent, and leads directly to corruption. And preventive and repressive measures to detect fraudulent reporting have not been done with the maximum on a cadre of both the political and the political party themselves. Such a situation would require the government to devise a strategy for the political party's financial checkups through forensic audits as applied in several countries, including Nigeria. The study aims to examine the model against the corruption of the political party done by Nigeria through its forensic audits and compartmentalizing its application in Indonesia. The author used normative-approach juridical methods with two approaches: the statute approach and comparative approach. The study raised two major issues. First, how is the corruption of political parties that occurred in Indonesia and Nigeria during the election period? Second, how does the forensic audit in Indonesia and Nigeria help to stop the corruption of the political party? Studies have shown that political corruption in both Indonesia and Nigeria consists mainly of bribery, votes buying, and cheating in reporting on party campaigns. The forensic audit is one of the most effective efforts to prevent and treat the political party's corruption through fraud detection coupled with increased independent forensic audit team to ensure healthy political finances.